2022
DOI: 10.1007/s00192-022-05104-w
|View full text |Cite
|
Sign up to set email alerts
|

No pelvic exam, no problem: patient satisfaction following the integration of comprehensive urogynecology telemedicine

Abstract: Introduction and hypothesisThe COVID-19 pandemic revolutionized the practice of medicine, requiring rapid adoption of telemedicine. However, patient satisfaction has not been well characterized for telemedicine visits for a broad range of urogynecologic conditions. Methods We performed a cross-sectional survey study following a retrospective review of all urogynecologic telemedicine visits from March 1, 2020, to March 31, 2021, at a tertiary care center. The survey queried patient satisfaction using the Likert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(31 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…11 Another study of 88 patients found high satisfaction of 94% with telehealth. 5 The two latter studies included new and returning patients. Although we were unable to demonstrate noninferiority, our findings provide supportive evidence of high patient satisfaction with telehealth for new visits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 Another study of 88 patients found high satisfaction of 94% with telehealth. 5 The two latter studies included new and returning patients. Although we were unable to demonstrate noninferiority, our findings provide supportive evidence of high patient satisfaction with telehealth for new visits.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, telehealth was used to reach patients with limited access to care, remotely monitor chronic medical conditions, and follow-up on hospital discharges. 2,4,5 In obstetrics and gynecology, telehealth has been used for the management of obstetric conditions, treatment and follow-up of family planning services, and the provision of perioperative care. 1 Data from other surgical subspecialties have further supported the use of telehealth for perioperative care.…”
Section: Why This Mattersmentioning
confidence: 99%
See 2 more Smart Citations
“…7 During the COVID-19 pandemic, abbreviated, virtual assessments for urinary symptoms were associated with high degrees of satisfaction (91% for fulfillment of personal needs, 94% overall satisfaction). 8 This highlights the value of validated symptom questionnaires that help establish a working diagnosis and treatment plan in the absence of a physical exam. Questionnaire-based diagnoses have acceptable accuracy for classifying UUI and SUI among women with uncomplicated medical and surgical histories and for initiating low-risk therapies for defined intervals.…”
Section: Making a Diagnosismentioning
confidence: 99%